Upaya Peningkatan Kualitas Hidup Lansia melalui Praktik Higiene Genital dan Skrining Mandiri Kesehatan - Riska Nuryana; Sulaiman Putra Nagaring; Muthmainnah Muthmainnah; Sumarmi Sumarmi (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
Older adults experience a decline in physiological function that increases their risk of various health problems, including infections resulting from inadequate genital hygiene and limited ability to perform self-health screening. Low health literacy further reduces their capacity for self-care, highlighting the need for community-based educational interventions to improve their quality of life. This community service program aimed to enhance older adults’ knowledge of genital hygiene, infection prevention, self-health screening, and early detection of disease warning signs. The program employed a one-group pretest–posttest design using a participatory educational approach. A total of 15 older adults aged 60 years and above in Gorontalo City were purposively selected as participants. Data were collected using a structured knowledge questionnaire and analyzed descriptively and comparatively. The results demonstrated a significant improvement in participants’ knowledge across all indicators, with the mean score increasing from 55.2 ± 8.4 on the pretest to 82.8 ± 6.2 on the posttest, representing a 49.5% improvement. The greatest increase was observed in genital hygiene (51.6%), followed by self-health screening (50.6%), recognition of disease warning signs (49.7%), and infection prevention (48.2%). Knowledge distribution shifted from predominantly low (60.0%) to high (73.3%), while the reduced standard deviation indicated more evenly distributed knowledge among participants. These findings suggest that participatory health education is effective in improving health literacy and supporting healthy aging.